Settings for the development of health literacy: A conceptual review - Catherine L. Jenkins; Jane Wills; Susie Sykes (Frontiers Media S.A., 2023)
Advances in conceptualizing settings in health promotion include understanding settings as complex and interlinked systems with a core commitment to health and related outcomes such as health literacy. Traditional settings for the development of health literacy include health care environments and schools. There is a need to identify and conceptualize non-traditional and emerging settings of twenty-first-century everyday life. The aim of this conceptual review is to inform a conceptual model of a "non-traditional" setting for the development of health literacy. The model uses the example of the public library to propose four equity-focused antecedents required in a setting for the development of health literacy: the setting acknowledges the wider determinants of health, is open access, involves local communities in how it is run, and facilitates informed action for health. The review concludes that a settings approach to the development of health literacy can be conceptualized as part of a coordinated "supersetting approach," where multiple settings work in synergy with each other.